Prevalence of Active Pouch Symptoms and Patient Perception of Symptom Control and Quality of Life in an Outpatient Practice - Polly Kirsch; Jessica Rauch; Olivia Delau; Jordan Axelrad; Shannon Chang; Aasma Shaukat (Gastro Hep Advances)
Background and Aims: Pouchitis is an inflammatory condition affecting the ileal pouch in patients’ status after ileal pouch anal anastomosis (IPAA). This affects a significant portion of IPAA patients. Our aim was to study the prevalence of active pouch symptoms among currently treated outpatients with endoscopic pouchitis and understand patients’ perspective of disease control and quality of life. Methods: We cross-sectionally reviewed the medical charts of patients who had undergone pouchoscopy at NYU Langone Health from 2010 to 2022 and recorded demographic, clinical, and endoscopic data. Based on the most recent data in the medical record, we defined active pouch symptoms as 2 or more current clinical symptoms and “endoscopic pouchitis” as “moderate” or “severe” by pouchoscopy. We also administered surveys in March 2023 to 296 patients with an IPAA to understand symptom control, quality of life, and interest in fecal microbiota transplant. Results: We identified 282 unique patients. The median age of patients was 46 (interquartile range 33–59), with 54.3% males. Of these, 37.2% of patients currently had active pouch symptoms, 36.9% had endoscopic pouchitis, and 14.9% met the criteria for both. Of the 296 surveys sent to patients with IPAA, 74 (25%) responded. The median age of respondents was 49.5 (interquartile range 34–62). 59.5% were male. Average treatment satisfaction score (scale of 0–10) was 6.4 and quality of life score was 5.8. A majority (64.9%) expressed interest in fecal microbiota transplant. Conclusion: Outpatients with active pouch symptoms or endoscopic pouchitis have high prevalence of active disease and report ongoing symptoms. The results underscore the inadequacy of current treatments and highlight the need for additional therapeutic options.